2017
DOI: 10.1111/conl.12409
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Landowners' Expectations May Hinder the Uptake of a Forest Certificate Trading Scheme

Abstract: A major challenge to reduce forest loss in the tropics is to incentivize conservation on private land in agricultural settings. Engaging private landowners in conservation schemes is particularly important along deforestation frontiers, such as in the southern Brazilian Amazon. While we know much about what motivates landowners to participate as providers, or sellers, of conservation schemes, understanding what motivates landowners who act as buyers, that is, those who require land to meet conservation obligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Particularly for sellers, price is related to forgone opportunity costs but that is not the case for buyers, who expect price to be much lower than sellers’ forgone opportunity costs (Giannichi et al. ). Perhaps at smaller scales, where opportunity costs are high, there would be even less averted loss and more restoration because sellers would expect high returns of their surplus, making restoration a less costly offset option for buyers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particularly for sellers, price is related to forgone opportunity costs but that is not the case for buyers, who expect price to be much lower than sellers’ forgone opportunity costs (Giannichi et al. ). Perhaps at smaller scales, where opportunity costs are high, there would be even less averted loss and more restoration because sellers would expect high returns of their surplus, making restoration a less costly offset option for buyers.…”
Section: Discussionmentioning
confidence: 99%
“…This option allows for a perpetual solution for buyers, which appears to be their preferred option (Giannichi et al. ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the economic literature on forest certification, market behaviors are the main focus, such as consumer cognition [12,13], cost and premium [14][15][16], market penetration [17,18], etc. Most studies from the national scope have generally claimed that forest certification has a negative impact on trade, such as Brazil [19], China [20][21][22], Chile [23], etc. From the limited existing evidences from a global perspective, Brenton [24] and Rametsteiner et al [25] identified that forest certification was not conducive to trade for developing countries and was likely to become a trade barrier from the perspective of ethical trade and political factors, respectively [5,19,26].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies from the national scope have generally claimed that forest certification has a negative impact on trade, such as Brazil [19], China [20][21][22], Chile [23], etc. From the limited existing evidences from a global perspective, Brenton [24] and Rametsteiner et al [25] identified that forest certification was not conducive to trade for developing countries and was likely to become a trade barrier from the perspective of ethical trade and political factors, respectively [5,19,26]. Therefore, the evidence of existing studies on the impact of forest certification on international trade in forest products is scattered and unclear in academia.…”
Section: Introductionmentioning
confidence: 99%